Modeling the effect of the addition of alumina on structural characteristics and tensile deformation response of aluminosilicate glasses - Benitez, Tobias; Rivas Murillo, John Sandro; de Ligny, Dominique; Travitzky, Nahum; Novaes de Oliveira, Antonio Pedro; Hotza, Dachamir (Ceramics International, 2020)
Aluminosilicate glasses, xAl2O3-(1-x)SiO2 with variable molar ratio 0 ≤ x ≤ 60%, were modeled by molecular dynamics (MD) in order to investigate the structural characteristics such as: coordination number and pair-angle distribution functions responsible for their mechanical performance. MD simulations showed that Si atoms coordinated to four O atoms are independently of the chemical composition. The number of O atoms coordinated to two decreased as the amount of Al2O3 is increased, while the opposite happened to O atoms coordinated to three. Al atoms coordinated to four O atoms were reduced as the amount of Al2O3 increases, whereas Al atoms coordinated to five O atoms were increased. Moreover, pair distribution function (PDF) study confirmed that the addition of Al2O3 causes densification of the aluminosilicate samples and, angle distribution function (ADF) corroborated PDF results and explained intermediate and long-range disorder structures of glasses. Assessment of the structural damage under uniaxial tension showed that aluminosilicate glasses are more capable of withstanding deformation without total structural failure than pure silica glasses.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Aluminosilicates; Armor; Glass-ceramics; Molecular dynamics